Memory and Its Impact on the Architectural and Social Structure of Cities - سعيد, سامر (Latakia University Journal -Engineering Sciences Series, 2020)
Cities are complex entities and constantly changing in which living is often conditional upon reminiscences that stimulate various emotions and sensations, unforgettable events make us long for a past or common memory in order to have the sense of belonging, perceptions and revivals of previous activities give a sense of coherence, consolidated vision and moving forward. Therefore, memory is the mental capacity through which events are stored, preserved and recalled, the architectural and urban structures work similarly to preserve human experiences through its connection with place and containment of individual and collective life events. The concept of memory associated also with a group of social studies brought out in the twentieth century which investigate the interrelation between memory and mankind and its role in keeping the continuance of life and creating a mnemonic connection between the past and future, and it also explores the repercussion of this interrelation on their environment. This is what the research will discuss in a form of trilogy centered on memory concept which combines different propositions starting with the viewpoint of several thinkers and sociologists that concerns about the concept of “collective memory” and its correlations and consequences on the built environment and human outcomes regarding architecture and cities, and then some architectural and urban planning theories developed in an influential ideological and social framework taking into account the concept of memory as an essential part of its content and considering the significance of the course of time and historical records in shaping cities and building upon its former findings, ending with practical experiments and applications of architectural designs dealing with the concept of memory explaining the methods and reasons of its transformation from normal structures to “memory carriers” and the impact of memory on the origination of these structures. The conclusion of the research clarifies the frameworks of the relationship between human and the city in the context of memory which is substantial to study when dealing with any architectural or urban situation.